Compatibilidade de Cordyceps javanica (Hypocreales: Cordycipitaceae) com pesticidas e sua virulência a mosca-branca Aleurodicus cocois (Curtis) (Hemiptera: Aleyrodidae) - Silva, Pedro Vitor Moura (2024)
The virulence of Cordyceps javanica was determined on eggs and nymphal stages of Aleurodicus cocois on cashew leaves in a screened house. Four bioassays were conducted with concentrations of 1×107, 1×108, 5×107, and 5×108 conidia mL-1 on eggs and 1st to 4th instar nymphs of A. cocois, with adults emerging from the latter treatment also evaluated. Fungal virulence was expressed and compared in terms of percentage mortality, confirmed mortality and estimated lethal time (LT50). The highest concentration of C. javanica could reduce egg hatching by ≤ 4%. Mortality of 1st instar nymphs ranged between > 60% and ≤ 87%, in 2nd instar > 61% and ≤ 77%, and in 3rd instar > 51% and ≤ 74%. Adult emergence was reduced by < 24% in all treatments. Nymphs treated with C. javanica also showed mortality confirmation values in all assessments. LT50 values were expressed in 1st to 3rd instar nymphs and in mortality confirmation of 4th instar nymphs. The fungus C. javanica caused confirmed mortality in the evaluated instars and in emerged adults of 4th instar nymphs treated by the fungus. The in vitro compatibility of C. javanica was evaluated with the highest dose of insecticides: Acetamiprid + Etofenprox; Deltamethrin; Spinetoram; Flupyradifurone, and fungicides: Melaleuca alternifolia; Sulfur; Difenoconazole; and Azoxystrobin + Difenoconazole registered for cashew trees, as well as the efficacy of C. javanica at 5 × 107 conidia/mL-1 sprayed alone or in combination with fungicides on 2nd instar A. cocois nymphs on cashew leaves. In vitro compatibility was investigated regarding conidial germination, vegetative growth, conidiogenesis, and colony-forming units (CFU). The efficacy of sprays was expressed as percentage mortality, confirmed mortality, and estimated lethal time (LT50) for the evaluated nymphs. Combinations with the insecticide Flupyradifurone and the fungicide M. alternifolia did not alter the development of C. javanica. The vegetative growth of C. javanica was not affected by combinations with insecticides, and combinations with M. alternifolia and Sulfur. Conidiogenesis was not affected by most combinations with insecticides but was by all combinations with fungicides. In CFU counting, only the combination with M. alternifolia did not differ from the control. Most combinations with fungicides had a negative impact on the infectivity capacity of C. javanica on A. cocois nymphs. Sprays using only the entomopathogenic caused mortality > 78% in nymphs, both alone and in combination with M. alternifolia. Mortality confirmation was observed in C. javanica + Difenoconazole: ≥ 3.9%; + Sulfur: ≥ 10.9%; + M. alternifolia: ≥ 65.1%. LT50 was determined for mortality and its confirmation in C. javanica alone and in combination with M. alternifolia.